Uma contribuição à análise da estrutura de custos na indústria de pequeno porte: a utilização do custo-meta por meio de um instrumento gerencial - Freitas, Luiz Henrique de (2007)
The small enterprises play a very important role in our national economy; however, well-known are their difficulties to remain alive in the market for a longer period of time. The problems of management have been pointed out as the factors which prevent them from growing and developing, and in the case of the small industries, one of their main difficulties lies in the incorrect way of analyzing their cost structure, leading them, sometimes, to non-satisfactory results. The objective of this study is to identify the necessary elements for the correct analysis of the costs structure of a small industry, using these elements to create a managerial instrument, applying, for this purpose, the concept of the target cost as well. This work starts with the characterization of the enterprise profile and the entrepreneur´s, explaining the need of a suitable costs management for the small companies. It also deals with the importance of the correct establishment of the sales prices. Finally, we purpose a managerial report directed to a suitable analysis of the costs structure of the small companies. We applied this report in a small industry of plastic branch, and we present the final results. Thus, we expect that our work may help the small entrepreneur make decisions based on more structuralized bases and not being dependent on his own feeling in order to direct the course of his enterprise